Cation functionalized nylon composite nanofibrous mat as a highly positive friction layer for robust, high output triboelectric nanogenerators and self-powered sensors. (October 2021) - Rana, S M Sohel; Rahman, M. Toyabur; Sharma, S.; Salauddin, M.; Yoon, Sang Hyuk; Park, Chani; Maharjan, P.; Bhatta, T.; Park, Jae Yeong
Abstract: Triboelectric nanogenerators (TENGs) have proven to be potential candidates for low-frequency vibration mechanical energy harvesting, which utilize different electron affinities material. In this regard, strong electron-donating tendencies materials are highly required to improve the TENGs' performance. Here, a poly(diallyldimethylammonium chloride) (poly-DADMAC)/nylon-11 composite nanofibrous mat is newly proposed as a highly positive triboelectric layer for boosting the TENGs' performance. Through the dielectric modulation of the nylon-11 nanofiber achieved by incorporating cationic poly-DADMAC, the output performance of the TENG was significantly enhanced by the relative dielectric constant, which is attributed to the three-fold increase in the surface charge trapping capability of the composite materials. After the incorporation of poly-DADMAC, the mechanical strength of the developed composite materials was six times greater than that of pristine nylon-11. The fabricated TENG showed excellent power density (7.6 W/m 2 ) and sustainable power generation for low-power electronic devices. The proposed TENG was successfully demonstrated as a self-powered pressure sensor with an ultra-high sensitivity of 1.01 V/KPa. Furthermore, the TENG was utilized as a self-powered motion sensor for monitoring real-time human motion, including slow walking, fast walking, jogging, slow running, fast running, and jumping. Finally, the TENG was adopted and demonstrated to successfully monitor human motion status using a smartphone web application in the Internet of Things (IoT). These results of this study are expected to provide guidance for the construction of high-performance TENGs and promote the development of self-sustainable portable or wearable electronics and self-powered sensors. Graphical Abstract: ga1 Highlights: A poly-DADMAC/nylon-11 composite nanofiber is newly developed for robust, high output triboelectric nanogenerators (TENGs). The poly-DADMAC/nylon-11 composite shows excellent charge trapping capability, stability, and mechanical strength. The fabricated TENGs exhibit excellent stability, durability (>86 k cycles), and extremely high-power density (7.8 W/m 2 ). The TENG was demonstrated as a self-powered pressure sensor with an ultra-high sensitivity of 1.01 V/KPa. TENG is successfully proven as a self-powered human motion sensor and power source for various low-power electronic devices.